Prenylated flavonoids and dihydrophenanthrenes from the leaves of Epimedium brevicornu and their cytotoxicity against HepG2 cells. Issue 19 (2nd October 2018) - Pang, Xu; Yin, Shuang-Shuang; Yu, Hai-Yang; Zhang, Yi; Wang, Tao; Hu, Li-Min; Han, Li-Feng
Abstract: Phytochemical study on the leaves of Epimedium brevicornu finally led to the isolation of four prenylated flavonoids (1 –4 ) and three dihydrophenanthrenes (5–7 ), of which1, 2, 5 and7 were new compounds. The structures of these compounds were established mainly by spectroscopic techniques, including NMR spectroscopy and mass spectrometry. These isolates exhibited the cytotoxic activities against HepG2 cells with the IC50 values of 32.8–87.3 μM. Abstract :